2022
DOI: 10.12998/wjcc.v10.i25.8827
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of six-step complex decongestive therapy for treating upper limb lymphedema after breast cancer surgery

Abstract: BACKGROUND Complex decongestive therapy (CDT) is currently recommended as the standard treatment for lymphedema. CDT is a four-step detumescence therapy that can effectively treat upper limb lymphedema after breast cancer surgery, and is considered non-invasive, painless and without side effects. AIM To determine the effectiveness of a six-step CDT involving a foam granule bandage for the treatment of upper extremity lymphedema pressure after breast cancer surgical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Pairwise meta-analysis suggested that BLC was superior to usual measures in all outcomes except VAS scores of swelling. This is inconsistent with previous study [58]. Perhaps due to the limited use of BLC treatment for BCRL in clinical practice, and insufficient sample size to support this [59].…”
Section: Plos Onecontrasting
confidence: 90%
“…Pairwise meta-analysis suggested that BLC was superior to usual measures in all outcomes except VAS scores of swelling. This is inconsistent with previous study [58]. Perhaps due to the limited use of BLC treatment for BCRL in clinical practice, and insufficient sample size to support this [59].…”
Section: Plos Onecontrasting
confidence: 90%
“…In our systematic literature search, 23 studies, including a total of 85,584 patients, were published since the review by Siotos et al on BCRL and breast reconstruction [124] . In various studies, the incidence of lymphedema was found to be lower in cases with breast reconstruction compared to mastectomy alone [125][126][127][128][129][130][131][132][133][134] , while other studies did not specify the incidence of lymphedema for breast reconstruction [31,122,[135][136][137][138][139] , type of reconstruction [128,129,140] , or BCRL incidence at all [31] . Figure 1 presents an overview of the incidence reported for BCRL in the different studies, where possible, by reconstruction type.…”
Section: Breast Cancer-related Lymphedema and Breast Reconstructionmentioning
confidence: 99%
“…Figure 1 presents an overview of the incidence reported for BCRL in the different studies, where possible, by reconstruction type. Further aspects emerged from the studies: Two recent large cohort studies published only as abstracts have found that delayed breast reconstruction (DBR) is significantly associated with reduced BCRL within ten years [127,131] . Both cohorts were extracted from the same 85,776,922 de-identified patient records.…”
Section: Breast Cancer-related Lymphedema and Breast Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations